Preparation of high-gradient ferromagnetic matrices for magnetic filters (separators) with fractal surface structure by magnetoelectrolysis - Gorobets, S.V.; Gorobets, O.Yu.; Bylo, O.N.; Potyomkin, M.M. (Functional Materials, 2009)
A method for steel etching under a magnetic field to obtain functional surfaces which are used as high-gradient ferromagnetic matrices of separators was describe. Розглянуто спосіб керування процесом травлення сталі під дією магнітного поля для отримання функціональних поверхонь, що застосовуються як високоградієнтні феромагнітні насадки сепараторів. Описан способ управления процессом травления стали под действием магнитного поля для получения функциональных поверхностей, которые применяются в качестве высокоградиентных ферромагнитных насадок сепараторов.